Bortezomib sensitizes primary human esthesioneuroblastoma cells to TRAIL-induced apoptosis - Koschny, Ronald; Holland, Heidrun; Sykora, Jaromir; Erdal, Hande; Krupp, Wolfgang; Bauer, Manfred; Bockmuehl, Ulrike; Ahnert, Peter; Meixensberger, Jürgen; Stremmel, Wolfgang; Walczak, Henning; Ganten, Tom M. (Journal of neuro-oncology, 2010)
TNF-related apoptosis-inducing ligand (TRAIL), a promising novel anti-cancer cytokine of the TNF superfamily, and Bortezomib, the first-in-class clinically used proteasome inhibitor, alone or in combination have been shown to efficiently kill numerous tumor cell lines. However, data concerning primary human tumor cells are very rare. Using primary esthesioneuroblastoma cells we analyzed the anti-tumor potential and the mechanism employed by Bortezomib in combination with TRAIL for the treatment of this rare but aggressive tumor. Expression of components of the TRAIL pathway was analyzed in tumor specimens and isolated primary tumor cells at the protein level. Cells were treated with TRAIL, Bortezomib, and a combination thereof, and apoptosis induction was quantified. Clonogenicity assays were performed to elucidate the long-term effect of this treatment. Despite expressing all components of the TRAIL pathway, freshly isolated primary esthesioneuroblastoma cells were completely resistant to TRAIL-induced apoptosis. They could, however, be very efficiently sensitized by subtoxic doses of Bortezomib. The influence of Bortezomib on the TRAIL pathway was analyzed and showed upregulation of TRAIL death receptor expression, enhancement of the TRAIL death-inducing signaling complex (DISC), and downregulation of anti-apoptotic proteins of the TRAIL pathway. Of clinical relevance, TRAIL-resistant primary tumor cells could be repeatedly sensitized by Bortezomib, providing the basis for repeated clinical application schedules. This is the first report on the highly synergistic induction of apoptosis in primary esthesioneuroblastoma cells by Bortezomib and TRAIL. This combination, therefore, represents a promising novel therapeutic option for esthesioneuroblastoma.